A based Cistanche deserticola polysaccharide functional-nanoparticle delivery system for effective oral vaccine to facilitate both systemic and mucosal immunity through enhancing oral delivery - Jin He; Tianyu Zhu; Lin Yu; Ningning Mao; Xuanqi Lu; Xiaofeng Shi; Xiangwen Deng; Yang Yang; Deyun Wang (Materials Today Bio)
Oral vaccines received great interest in preventing of global pandemics due to the ability to facilitate both systemic and mucosal immune responses. However, the enzymatic degradation, low permeability of mucus barrier, and lack of effective and safe mucosal adjuvants continue to remain significant challenge for oral vaccine. Herein, we developed a novel delivery system based on nanoparticles functionalized by plant polysaccharides to address the above challenges. Firstly, the Cistanche deserticola polysaccharide (CDP) functional-dendritic fibrous nano-silica (DFNS) nanoparticles (CDP-DFNS) were prepared. Encouragingly, the CDP-DFNS with prominent physicochemical and structural characteristics showed high cellular uptake and lead to a high transmembrane transport and intestinal epithelium permeability of antigen. Furthermore, CDP-DFNS significantly induced the antigen internalization and activation of dendritic cells after transport across epithelial cells. In addition, the in vivo experiment results reveled that CDP-DFNS was efficiently facilitated both antigen-specific systemic and mucosal immunity. In conclusion, CDP-DFNS represents a promising candidate for oral vaccine delivery, offering a unique combination of carrier and adjuvant properties. However, further research is needed to evaluate its efficacy in larger animal models and human clinical trials to confirm its translational potential, and fully establish its potential as a next-generation oral vaccine platform.